2022
DOI: 10.26434/chemrxiv-2022-vbl5d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data-Driven Analysis of High-Throughput Experiments on Liquid Battery Electrolyte Formulations: Unraveling the Impact of Composition on Conductivity

Abstract: An in-house, unique, custom-developed high-throughput experimentation facility, used for discovery of novel and optimization of existing electrolyte formulations for diverse cell chemistries and targeted applications, follows a high-throughput formulation-characterization-performance-elucidation-optimization-evaluation chain based on a set of previously established requirements. Here, we propose a scalable data-driven workflow to predict ionic conductivities of non-aqueous battery electrolytes based on linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The overall workflow of the herein presented automatic coin cell assembly robot focuses on the production process after electrode coating and electrolyte formulation. Though the system is principally amendable to manufacturing cells with different electrolyte mixtures 19,20 and electrodes, the herein presented study uses the same electrolyte (1M LiPF6 in 3:7 EC:EMC by weight formulated by Elyte, Germany) and electrodes throughout.…”
Section: Materials Preparationmentioning
confidence: 99%
“…The overall workflow of the herein presented automatic coin cell assembly robot focuses on the production process after electrode coating and electrolyte formulation. Though the system is principally amendable to manufacturing cells with different electrolyte mixtures 19,20 and electrodes, the herein presented study uses the same electrolyte (1M LiPF6 in 3:7 EC:EMC by weight formulated by Elyte, Germany) and electrodes throughout.…”
Section: Materials Preparationmentioning
confidence: 99%
“…The dataset DS1 used herein is the same underlying the study presented by Flores et al [13] using the formulation and characterization setup reported by Krishnamoorthy et al [14] The herein presented one-shot active learning approach is model free, meaning that we do not utilize any physics or chemistry knowledge except correct pose of the input (formulation) and output (conductivity) and a compartmentalization of the problem by temperature.…”
Section: Pre-shot Model Trainingmentioning
confidence: 99%
“…The studies by Dave et al [11,12] consider a wide range of electrolyte formulations but within a narrow range of temperatures. Utilizing an existing dataset [13,14] spanning a wide range of formulations and temperatures, we aim to perform as few as possible additional experiments to discover formulations with maximum conductivity for a wide range of temperatures. This is performed in a workflow called one-shot active learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In essence, SR simultaneously learns both adjustable parameters and the functional form relating electrolyte conductivity with its formulation. We make use of a HTE setup 30 to collect thousands of conductivity measurements of LiPF 6 -based electrolytes with ethylene carbonate (EC), propylene carbonate (PC) and ethyl methyl carbonate (EMC) as solvents at different temperatures. With a simple SR approach, we train multiple candidate expressions and show that a particular expression emerges as a clear candidate, complying with strict and often competing criteria of accuracy, simplicity and consistency.…”
Section: Introductionmentioning
confidence: 99%